An experimental investigation of fly ash – GGBS based high strength geopolymer concrete incorporating copper slag - Khan, S. Imran; Brindha, D.; Muthuramu, K.L. (Journal of Structural Engineering, 2024)
Geopolymer concrete can be considered as a Green building technology that serves as an alternative for cement and river sand by using Alkaline Activator Solutions (AAS) and Copper Slag (CS). To attain High Strength Geopolymer Concrete (HSGC) trial tests were carried out by creating eleven different mix proportions with replacement of binder material fly ash by Ground Granulated Blast Furnace Slag (GGBS) from 0% to 100% by weight at increments of 10%. Alkaline activator solutions (14 molar Sodium Hydroxide and Sodium Silicate) were used in this study for polymerization. In each different mix proportion, specimens were cast and heat curing was done by maintaining 70 degree Celsius for 24 hours. The specimens were tested for strength parameters like compressive strength, split tensile strength and flexural strength. From the test results, combination of 60% GGBS and 40% fly ash produced high compressive strength of 71 N/mm². Further, an attempt was made with the same proportion of binder material and by replacement of river sand with Copper slag from 0% to 100% by weight at increments of 10%, eleven different mix proportions were made. It is understood from the strength test results, substitution of 50% copper slag by sand yielded a high compressive strength of 77 N/mm². Thus, the above mix combination resulted in high strength geopolymer concrete.